Role of biochar as an additive in organic waste composting. (January 2018) - Sanchez-Monedero, M.A.; Cayuela, M.L.; Roig, A.; Jindo, K.; Mondini, C.; Bolan, N.
Highlights: Biochar enhances environmental conditions for microbial growth in composting piles. Key biochar properties include porosity, surface area and cation exchange capacity. Biochar application at 10% is recommended for optimum composting performance. Biochar at 10–30% rates succeeded in mitigating NH3, N2 O and CH4 emissions. Biochar decreased bioavailability of Cu and Zn in composts. Abstract: The use of biochar in organic waste composting has attracted interest in the last decade due to the environmental and agronomical benefits obtained during the process. Biochar presents favourable physicochemical properties, such as large porosity, surface area and high cation exchange capacity, enabling interaction with major nutrient cycles and favouring microbial growth in the composting pile. The enhanced environmental conditions can promote a change in the microbial communities that can affect important microbially mediated biogeochemical cycles: organic matter degradation and humification, nitrification, denitrification and methanogenesis. The main benefits of the use of biochar in composting are reviewed in this article, with special attention to those related to the process performance, compost microbiology, organic matter degradation and humification, reduction of N losses and greenhouse gas emissions and fate of heavy metals.